Green Sustainable NYSE Companies: Trading the Offerings - , Vasiliki A. Basdekidou (Archives of Current Research International, 2017)
Trading should be regarded as a chaotic system with many benchmarked group of companies (e.g. green sustainable firms), company initiatives (e.g. NYSE equity offerings: IPOs), and temporally dynamics functions supported by timing technical analysis functionalities (like open gaps, morning breakouts, etc.). These functionalities offer great trading opportunities in correct timing situations and for right side of the trade (long, short) positions; and they are defined as temporal trading functionalities. This paper, based on empirically-tested data, contributes to knowledge and trading community by examining the IPOs functions of green (environmentally friendly) sustainable companies, as they projected in time (temporal NYSE offerings); and investigate and define innovative temporal trading functionalities useful in technical analysis trading strategies. Paper concludes that in NYSE IPO offerings trading, regarding green sustainable companies, the long-term corporate passive investors are benefit well at the expense of corporate swing traders, short-term active traders and intraday speculators.